Biopreservation of living tissue engineered nerve grafts. (August 2021) - Shultz, Robert B; Katiyar, Kritika S; Laimo, Franco A; Burrell, Justin C; Browne, Kevin D; Ali, Zarina S; Cullen, Daniel K
Tissue engineered nerve grafts (TENGs) built from living neurons and aligned axon tracts offer a revolutionary new approach as "living scaffolds" to bridge major peripheral nerve defects. Clinical application, however, necessitates sufficient shelf-life to allow for shipping from manufacturing facility to clinic as well as storage until use. Here, hypothermic storage in commercially available hibernation media is explored as a potential biopreservation strategy for TENGs. After up to 28 days of refrigeration at 4℃, TENGs maintain viability and structure in vitro . Following transplantation into 1 cm rat sciatic defects, biopreserved TENGs routinely survive and persist for at least 2 weeks and recapitulate pro-regenerative mechanisms of fresh TENGs, including the ability to recruit regenerating host tissue into the graft and extend neurites beyond the margins of the graft. The protocols and timelines established here serve as important foundational work for the manufacturing, storage, and translation of other neuron-based tissue engineered therapeutics.